AutoCAD 2010 (3KfGFj hKdGKj GdCHYGOs ((3GdbGgQIs (3KQj Oj ceHjhJQ SfJQs, 2010)
(3CcKQ ef (B70 (3OQS jMJhj Ydi TQM dLejY ChGeQ HQfGeL (BAutoCAD 2010 (3KfGFj hKdGKj GdCHYGO eLehYI ef GdJWHjbGJ GdeJbOeI ddhUhd deSJhi GdEMJQGas
(3GdJYdje HGddZI GdYQHjIs
(3GdMO GdCOfi deJWdHGJ GdJTZjd (Bwindows( xp-vista-win 7)(3, cGQJ UhJs
Keywords: autocad -- (3JYdes -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs